Sharia Promotion Strategy in Fashion Business Competition (Study on Mayang Collection Malang) - Ika Rinawati; Syifaun Nuroh (Yayasan Adra Karima Hubbi, 2024)
Background. Muslim fashion products have quite a big opportunity because the fashion industry is one sector that is able to show development in increasing the country's economic growth. On the other hand, in reality business in the fashion sector does not always increase, because this business sector opens up opportunities for the entry of new competitors. Purpose. The aim of the research is to examine sharia promotional strategies which aim to provide references regarding promotional strategies in the Mayang Collection business competition. Method. This research method uses qualitative research methods with a case study approach and data collection techniques using interview techniques, observation and documentation, data analysis techniques using data reduction, data presentation and drawing verification conclusions. Results. The results of the research show that sharia promotional strategies can be applied to 5 marketing mixes, including advertising that is seen applying the practice of shiddiq (principle of honesty), personal sales that is seen applying tabligh (communication intelligence), sales promotion by giving istikomah discounts, direct marketing by applying Fathonah's nature is to provide correct information about its products. Conclusion. The conclusion of this research is that Mayang carries out sharia promotional activities in accordance with what Islam teaches, including first, advertising. In advertising, Mayang does it honestly and says that the products it sells are in accordance with reality. Second, personal marketing, Mayang Collection carries out promotions in the form of personal marketing. Third, public relations, in this case, may not promote sharia in the field of public relations. The four sales promotions carried out by Mayang Collection provide promotions at certain times and also provide bonuses or prizes for customers who have purchased Mayang Collection products. The five direct marketing activities carried out by Mayang Collection Gondanglegi are direct marketing activities.